The role of gene copy number variation in antimicrobial resistance in human fungal pathogens - Adarsh Jay; David F. Jordan; Aleeza Gerstein; Christian R. Landry (npj Antimicrobials and Resistance)
Abstract Faced with the burden of increasing resistance to antifungals in many fungal pathogens and the constant emergence of new drug-resistant strains, it is essential to assess the importance of various resistance mechanisms. Fungi have relatively plastic genomes and can tolerate genomic copy number variation (CNV) caused by aneuploidy and gene amplification or deletion. In many cases, these genomic changes lead to adaptation to stressful conditions, including those caused by antifungal drugs. Here, we specifically examine the contribution of CNVs to antifungal resistance. We undertook a thorough literature search, collecting reports of antifungal resistance caused by a CNV, and classifying the examples of CNV-conferred resistance into four main mechanisms. We find that in human fungal pathogens, there is little evidence that gene copy number plays a major role in the emergence of antifungal resistance compared to other types of mutations. We discuss why we might be underestimating their importance and new approaches being used to study them.